Efektivitas Program Edukasi Gizi terhadap Pengendalian Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe 2 - Muhammad Akbar; Diana Kurnaini (Journal of Applied Health Sciences, 2025)
Type 2 Diabetes Mellitus is a global health problem characterized by elevated blood glucose levels due to insulin resistance and impaired insulin secretion. Blood glucose control does not rely solely on pharmacological therapy but also requires non-pharmacological interventions, one of which is nutrition education programs. This study aimed to analyze the effectiveness of nutrition education programs in controlling blood glucose levels among patients with Type 2 Diabetes Mellitus. A quasi-experimental design with a pre-test and post-test control group approach was employed. The study sample consisted of 60 patients, divided into an intervention group (n=30) and a control group (n=30), selected using purposive sampling. The intervention consisted of a 4-week intensive nutrition education program, covering topics such as balanced diet, selection of complex carbohydrate sources, portion management, and the importance of physical activity. The results revealed a significant reduction in fasting blood glucose levels in the intervention group compared to the control group (p < 0.05). Moreover, patients’ knowledge and dietary adherence in the intervention group significantly improved after receiving the education program. These findings demonstrate that nutrition education effectively enhances patients’ knowledge while supporting blood glucose control. In conclusion, nutrition education programs can serve as a complementary strategy for the comprehensive management of Type 2 Diabetes Mellitus.